A Study On the Romanians’ Profile Among Leisure Activities - Smaranda Cosma; Konstantina Zerva; Marius Bota; Cristina Fleșeriu (Amfiteatru Economic)
Nowadays, there is an increased concern about what leisure is and how people spend their leisure time. When we are talking about leisure, all of us have “images” in our minds; different from person to person. These are images of freedom out of constrains and obligations. The purpose of the research is to identify and describe the leisure activities among the Romanians and the influence of respondents’ profile in respect with their preferences. As a research method, the descriptive research based on investigation was used. For data collection, an interview based on a short questionnaire was implemented for several months during the year of 2015 and 2016. The research reveals that in average the respondents spent 4,6 hours engaged in leisure activities in a working day and 9,3 hours in a free day. In a working day, the most frequent leisure activity is surfing on the internet (more than 60% of the respondents) and the rarest is visiting tourist attractions or destinations (almost 39%). In a free day, ones again, surfing on the internet (61% respondents) is the most frequent leisure activity and the rarest one is participating at cultural activities like visits at the museum, art galleries etc. (36.53%). The study shows that the respondents prefer non-home-based leisure activities and also active ones